Goddess symbolically embodied by a facemask - Mumbai Archive Project Team (Jio Institute, 2024)
The Goddess is symbolically embodied by a facemask that is attached to the tree trunk, serving as the deity’s body. A horizontal pole extends from the trunk, representing the Goddess’s arms. This arrangement gives Holika an anthropomorphic form, which is worshipped by devotees.